Psychosocial Factors at Work and Occupational Injury: Results From the French National SUMER Survey. Issue 3 (March 2015) - Lesuffleur, Thomas; Chastang, Jean-François; Sandret, Nicolas; Niedhammer, Isabelle
Abstract : Objective: This study aims at exploring the associations between psychosocial work factors and occupational injury. Methods: The study was based on 46, 962 employees of the French national representative survey SUMER 2010. The associations between psychosocial work factors and occupational injury/absence duration for injury within the last year were studied using weighted logistic and negative binomial regression models adjusted for covariates. Results: Verbal abuse and low predictability for both sexes, psychological demands for women and low reward, physical violence, and bullying for men were associated with occupational injury. Low decision latitude and psychological demands for women were associated with absence duration for injury. Conclusions: Some psychosocial work factors may play a role in occurrences of occupational injury, but the role is unclear in relation to absence duration for injury.